Validation of the Gap-fill as an Overall Measure of English Language Proficiency among Iraqi EFL Learners - Sattar, Ahmed (Thi Qar Arts Journal, 2024)
The purpose of this study was to validate the Gap-fill among Iraqi EFL university students. To this end, two types of multiple-choice Gap-fill were administered to a sample of EFL students along with a number of other tests as criteria. Correlational analyses revealed moderate to strong correlations between the Gap-fill and the criterion measures. Principal components analysis resulted in a one-factor solution with the Gap-fill highly loading on this single factor. These were interpreted as validity evidence for the. Gap-fill Implication of the study for classroom testing are discussed.  Keywords: Gap-fill, reduced redundancy principle, validity, conversational Gap-fill, written Gap-fill